Generalized estimating equations for modeling cluster randomized trial data on smoking cessation among tuberculosis patients - Vasantha Mahalingam; Ratnakar Singh; Ramesh Kumar Santhanakrishnan; Adhin Bhaskar; Ponnuraja Chinnaiyan (PLoS ONE, 2025)
There is a paucity of studies applying Generalized Estimating Equations (GEE) for longitudinal analysis of smoking cessation outcomes within the framework of a cluster randomized trial, especially among tuberculosis (TB) patients. In this study, a GEE model which accounts for repeated measures and cluster-level effects was implemented to identify factors associated with smoking cessation among TB patients. The data included 375 TB patients who were smokers and given TB treatment during 2013–2016 in Kanchipuram and Villupuram districts under a cluster randomized trial. GEE modeling provided robust, population-averaged estimates while accounting for intra-cluster correlation, confirming the sustained impact of these interventions. The model demonstrated that smoking cessation interventions, when integrated with TB treatment, had an impact on cessation outcomes in these populations.